Intravenous thrombolysis in Thai patients with acute ischemic stroke: Role of aging - Pornpatr A. Dharmasaroja (2018)
Background: Intravenous thrombolysis is a standard treatment in eligible acute ischemic stroke (AIS) patients. However, the advisability of treating patients >80 years of age is still debated. The aim of this study was to evaluate the role of aging on the outcomes in Thai patients treated with intravenous thrombolysis. Methods: Patients with AIS treated with intravenous recombinant tissue-plasminogen activator (rtPA) between June 2007 and November 2010 were included. The demographics and measured outcome variables were compared between patients ≤70 and >70 years of age. Patients were also classified into 4 subgroups by the age ranges: ≤60 years, 61 to 70 years, 71 to 80 years, and ≥81 years of age. Results: Two hundred sixty-one patients were included. Seventeen patients (6.5%) were >80 years old. Higher mortality (20.2% vs 5.1%; P <.001) and symptomatic intracerebral hemorrhage (7.7% vs 1.2%; P =.004) were found in the patients >70 years of age when compared with younger patients, and the rate of favorable outcome was lower (38.1% vs 55.4%; P =.010). Higher mortality rates were seen with increasing age: 3%, 8%, 20%, and 21% in patients aged ≤60, 61 to 70, 71 to 80, and ≥81 years of age, respectively. Conclusions: Thai stroke patients >70 years of age may carry a higher risk of mortality when treated with intravenous rtPA compared to patients ≤70 years of age. © 2013 by National Stroke Association.